2012
DOI: 10.1021/ja3037349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Bonds on pKa Values: Importance of Networking

Abstract: The pK(a) of an acyclic aliphatic heptaol ((HOCH(2)CH(2)CH(OH)CH(2))(3)COH) was measured in DMSO, and its gas-phase acidity is reported as well. This tertiary alcohol was found to be 10(21) times more acidic than tert-butyl alcohol in DMSO and an order of magnitude more acidic than acetic acid (i.e., pK(a) = 11.4 vs 12.3). This can be attributed to a 21.9 kcal mol(-1) stabilization of the charged oxygen center in the conjugate base by three hydrogen bonds and another 6.3 kcal mol(-1) stabilization resulting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 72 publications
7
72
0
Order By: Relevance
“…For each sample (FB200-FB700), there were some differences among their individual inflection points (named pH d1 and pH d2 , marked in Figure 2). For instance, pH d1 and pH d2 for FB300-FB400 were located at pH values of 5 and 9, respectively, while the pH d1 and pH d2 for the high temperature samples appeared at pH values of 6 and 10, respectively; this effect can be ascribed to the effects of substrate structure on the dissociation of functional groups, 47,48 and the obtained structural characteristics showed significant differences in functional group dissociation for biochars produced at different temperatures. Coupled with FTIR spectra of −OH and −COOH bands on biochars, the pH d1 and pH d2 correspond to the dissociation of carboxyl and hydroxyl groups, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 91%
“…For each sample (FB200-FB700), there were some differences among their individual inflection points (named pH d1 and pH d2 , marked in Figure 2). For instance, pH d1 and pH d2 for FB300-FB400 were located at pH values of 5 and 9, respectively, while the pH d1 and pH d2 for the high temperature samples appeared at pH values of 6 and 10, respectively; this effect can be ascribed to the effects of substrate structure on the dissociation of functional groups, 47,48 and the obtained structural characteristics showed significant differences in functional group dissociation for biochars produced at different temperatures. Coupled with FTIR spectra of −OH and −COOH bands on biochars, the pH d1 and pH d2 correspond to the dissociation of carboxyl and hydroxyl groups, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 91%
“…As a result, optimization of all structures was performed in H 2 O (water), DMSO (dimethyl sulfoxide), and CH 3 CN (acetonitrile) using PCM model and B3LYP/6‐311++G(d,p) level of theory. Prediction of p K a values in H 2 O, DMSO, and CH 3 CN was performed using Eqn , where [∆ Gitalicrxn0.25em° (kcal/mol)]/1.364 = p K a (HX) − p K a (CH 3 SO 3 H) or p K a (HX) = p K a (CH 3 SO 3 H) + [∆ Gitalicrxn0.25em° (kcal/mol)]/1.364 HX+CitalicH3SitalicO3italicX+CitalicH3SitalicO3H…”
Section: Computational Detailsmentioning
confidence: 99%
“…Therefore, determining p K a values computationally has become a subject of extensive interest. For instance, we have recently studied the effect of hydrogen bond on p K a values of heptol and a series of polyols in DMSO …”
Section: Introductionmentioning
confidence: 99%
“…[11] In particular, addition of Zn 2 + to a manganese(V)-oxo corrolazine system changed the electronic state to a manganese(IV)oxo corrolazine cation radical and improved its catalytic properties through valence tautomerism. [17] Recent studies of Kass an co-workers [18] showed that intramolecular hydrogen bonding can dramatically influence the pK a values of molecules and thereby play a key role in reactivities. [13] In one of these studies, Borovik and co-workers focused on metal-oxo complexes, [M IV (O)A C H T U N G T R E N N U N G (H 3 buea)] À (M = Fe, Mn; H 3 buea = tris[N'-tert-butylureayl-N-ethylene]amine; Scheme 1).…”
Section: Introductionmentioning
confidence: 99%